Enzymatic unhairing: Permeability assay of bovine skin epidermis with fungal enzyme extracts - Galarza, Betina Claudia (2019)
The aim of enzymatic unhairing is to allow the separation of the outer sheath of hair root from the dermal connective tissue. This is considered an ecofriendly process. It?s not expensive since if the enzymes are applied on the epidermis thereby surface extracts could be saved. The purpose of this work was to analyze the changes in pilosebaceus unit and basal lamina by unhairing enzyme action. Various keratinolytic fungi, previously isolated and selected from different soil samples were used: Neurospora crassa, Verticillum albo-atrum, Trichophyton ajelloi, Chrysosporium sp, Aspergillus sydowii, Paecilomyces lilacinus and Acremonium murorum. Fungal isolates were cultivated in solid state conditions using hair waste obtained from the hair-saving unhairing process as substrate. Enzyme extracts were characterized according to their keratinolytic-proteolytic activity and protein content. Bovine skins were placed in plastic plates where the epidermis contacted with different solutions: fungal enzyme extracts with commercial tensioactives (0.1%, 0.5%), biocide 0.2% w/w (wet skin) for 4 h (soaking) and 24 h (unhairing) at 25°C and 40 rpm. Samples of skin with and without enzymatic treatment were fixed in 4% formaldehyde, dried on increasing concentration of ethanol and analyzed with scanning electron microscopy. It was observed that the enzymes altered the epidermis, caused detachment of corneocytes and the emptying of hair follicles. Characteristic patterns of hair cuticle and collagen fibres were preserved in skin control with buffer. Trichophyton ajelloi caused the strongest depilatory effect . It was concluded that the enzyme penetration through epidermis could be employed for the application of reagents during the handcrafted tanning of leather.